EFEKTIVITAS MANAJEMEN STRATEGIK DALAM PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The purpose of this study is to explain how the effectiveness of strategic management in Badan Usaha Milik Desa (BUMDes). The type of research used is qualitative research that aims to collect information from a number of respondents or informants who are considered to provide information related to the research problem determined by purposive sampling, namely to determine the informants capable of representing a number of informants needed. The results of the research obtained that Badan Usaha Milik Desa (BUMDes) in Patalassang village has not been effective to help the independence of the village because the management of existing BUMDes has not run maximally this is due to the expertise of the board of BUMDes also still relatively low